Analisis Manajemen Keamanan Informasi Menggunakan Standard ISO 27001:2005 Pada Staff IT Support Di Instansi XYZ - Kristanto, Titus; Sholik, Mohammad; Rahmawati, Dewi; Nasrullah, Muhammad (Universitas Trilogi, 2019)
Information security management is very important to use, especially for educational instutions, because it is able to reduce the risk of threats to the use of information technology for educational organizations. Information security management is indispensable as an effort to minimize the risk of data enhancement and information threats. Implementation of information security management is intended to know technical problems and non technical problems. The research uses the ISO 27001:2005 standard is very flexible depending on the needs of the organization and focus on information security management. The research results using the ISO 27001:2005 standard is able to reduce the risk level and perform some activities that must be improved to improve information security at XYZ institutions.